KARAKTERISTIK MINUMAN BIR PLETOK BERKARBONASI DENGAN PERBEDAAN KOMPOSISI JENIS RIMPANGNYA - Siti Nur Kholishoh; Ria Ulfiasari; Niko Kurniawan; Iffah Muflihati (Department of Food Technology, Universitas Pasundan, Bandung, 2020)
This research aimed to study the characteristics of carbonated bir pletok with different types of rhizome composition. The research design used factorial randomized design with 1 factor, it’s the type of rhizome which comprised of javanese turmeric, cutcherry, and fingerroot. Carbonated bir pletok was analysed of total dissolved solids, color and sensory analysis. The total dissolved solids of Carbonated rhizome drinks range from 5.76 to 8.13 ˚brix. Color analysis showed no significant difference (p <0.05) on the level of brightness (L *) and the level of redness (a *). While the yellowish level (b *) showed a significant difference (p> 0.05) between rhizome drinks samples (javanese turmeric, cutcherry, and finger root) to the control. Brightness level (L *) ranges from 42,236-38,182. The redness level (a *) ranges from 55,212-59,135. The yellowish level (b *) ranges from 7,6323-21,586. The result of hedonic analysis showed fingerroot bir pletok rather liked. Hedonic characteristics of fingerroot bir pletok for color intensity, ginger aroma, bitter flavor, pungent flavor, carbonation and overall of 3.80, 3.93, 3.10, 3.16. dan 3.70 respectively. The results of descriptive analysis showed the treatment of javanese turmeric, cutcherry, and fingerroot were not significantly different from the control (p <0.05) on the carbonation parameters. While the parameters of color intensity, ginger aroma, bitter flavor, pungent flavor showed significant differences (p> 0.05).